2018
DOI: 10.30634/2414-2077.2017.03.5
|View full text |Cite
|
Sign up to set email alerts
|

CuPd Bimetallic Nanoparticles Supported on Magnesium Oxide as an Active and Stable Catalyst for the Reduction of 4-Nitrophenol to 4-Aminophenol

Abstract: Abstract:In this work, we report the synthesis and characterization of a catalyst based on bimetallic CuPd nanostructures generated over a magnesium oxide support. Its catalytic activity and reusability have been tested in the reduction of 4-nitrophenol as a model reaction using NaBH4 as the source of hydrogen for the reduction of the nitro-group. The structure, composition and morphology of the catalysts were studied by N2 physisorption, X-ray diffraction (XRD), Transmission Electron Microscopy (TEM) and X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…47 Nevertheless, Cu 1+ is assumed to be present in the Li(HEO)F compound. The peak at 1303.8 eV in the Mg 1s spectrum can be attributed to Mg 2+ , 48,49 and the Zn 2p 3/2 at 1021.3 eV and Zn LMM at 988.6 eV are indicative of Zn 2+ . [50][51][52] 'NaCl' has also been successfully added to the HEO structure through an identical ball-milling approach.…”
Section: Materials Characterizationmentioning
confidence: 97%
“…47 Nevertheless, Cu 1+ is assumed to be present in the Li(HEO)F compound. The peak at 1303.8 eV in the Mg 1s spectrum can be attributed to Mg 2+ , 48,49 and the Zn 2p 3/2 at 1021.3 eV and Zn LMM at 988.6 eV are indicative of Zn 2+ . [50][51][52] 'NaCl' has also been successfully added to the HEO structure through an identical ball-milling approach.…”
Section: Materials Characterizationmentioning
confidence: 97%
“…Additionally, an extra peak is observed at 646.3 eV, representing the satellite peak of the Mn 2p 3/2 main peak. Figure d displays the Mg 1s XPS spectrum. The peak at 1303.7 eV is associated with the chemical environment of Mg(1) in Mg(1)­(OH) 6 coordination. From the XPS diffraction patterns, it can be observed that there is only one environment for Mn and Mg throughout the entire crystal structure.…”
Section: Resultsmentioning
confidence: 99%
“… 36 The Mg XPS spectrum generally uses Mg 1s to analyze the oxidation state, which is located between 1302 and 1305 eV. 37 However, the binding energy of Mg 1s is out of the scan range of the equipment we used in this study. Therefore, Mg 2p was used for the Mg oxidation state analysis.…”
Section: Resultsmentioning
confidence: 99%